(untitled) (American Journal of Islam and Society, 2002)
Islam in Global History, written in two volumes covering the period from the death of the Holy Prophet to the First World War, has the distinction of being a book on history and the philosophy of history. This is because, as the reader discovers, it is not merely a chronicle of events of the Muslim world from the advent of Islam to the end of the World War I; it is a book which provides insights into the causes of the victories and defeats of dynasties as well as successes and failures of movements in Islamic history, and lays down the laws for the rise and fall of civilizations. Certainly, he is not the first in the field of the philosophy of history. The two stalwarts who made original and remarkable contributions in this field during the last two millennia are Ibn Khaldun and Arnold Toynbee. The books in which they propounded their theories of the interpretation of history are not books on history as such. Historical data were, no doubt, used and analyzed to substantiate their theses. lbn Khaldun proved his concept of asabiyah (social group cohesion) in the context of the history of the Arabs and the Berbers, which he was to write subsequently. Toynbee used the data from world history to prove his idea of "Challenge and Response" to be the detennining factor in the strength and decay of civilizations and societies. It is to the author’s credit that such a comprehensive and coherent work on Islamic history has been produced. At each critical stage he diagnosed the causes of the major events that went into making watersheds and turning points in Muslim history worldwide. Dr. Ahmed is an eclectic writer who has partially benefited from the concepts of the interpretation of history expounded by lbn Khaldun and Toynbee. For example, he agrees with lbn Khaldun when he says: The origins of the Ottoman Empire are to be found in a combination of Turkish ’asabiyah, a term used by lbn Kha Idun to denote tribal cohesion, the force that holds together tribes through bonds of blood, a characteristic found in abundance among peoples of the desert and the nomads off the steppes. He concurs with Toynbee when he writes: Great civilizations measure up to their challenges and grow more resili ent with each crisis, turning adversity into opportunjty. Critical moments in ...